Structural phase transition associated with van Hove singularity in 5d transition metal compound IrTe2 - T Qian; H Miao; Z J Wang; X Shi; Y B Huang; P Zhang; N Xu; L K Zeng; J Z Ma; P Richard; M Shi; G Xu; et al. (New Journal of Physics, 2014)
We have investigated the electronic states of IrTe _2 by using angle-resolved photoemission spectroscopy to elucidate the origin of the structural phase transition. Both the Ir 4f and Te 4d core level spectra exhibit dramatic splitting below the phase transition temperature T _s , suggesting that there exist two inequivalent Ir and Te sites with distinctly different electronic states in the distorted phase. The band related to the saddle points at the Fermi level ( E _F ) is strongly reconstructed, which removes the van Hove singularity from E _F below T _s . The wavevector connecting the adjacent saddle points is consistent with the in-plane superstructure modulation wavevector. These results indicate that the phase transition in IrTe _2 is intimately associated with the saddle points. As the van Hove singularity mainly originates from the Te p _x + p _y orbitals, the Te 5p electronic states play a dominant role in the structural phase transition.